Ferrous burden behaviour under nut coke mixed charge conditions. (25th November 2020) - Gavel, Dharm Jeet; Adema, Allert; van der Stel, Jan; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
ABSTRACT: Effect of nut coke addition with ferrous burden (pellet and sinter mixture) is experimentally investigated under simulated blast furnace conditions. Nut coke mixing degree was varied (0, 20 and 40 wt-%) as a replacement of the regular coke. During smelting, the ferrous bed evolves through three distinct stages of shrinkage due to indirect reduction, softening and melting, respectively. Nut coke increases the reduction kinetics, limits softening and enhances iron carburization in the ferrous bed to affect all three stages. Additionally, nut coke physically hinders the sintering among the ferrous burden to keep the interstitial voids open, which exponentially increases the gas permeability. A significant impact of nut coke mixing occurs in the cohesive zone temperature range, which is decreased by 77°C upon addition of 40 wt-% nut coke. Various experimental results give supports for the extensive utilization of nut coke as a replacement of regular coke in the blast furnace.